السياسة الفرنسية المتبعة في تفكيك الملكية العقارية الجزائرية 1830- 1900م وانعكاساتها على المجتمع الجزائري - رواحنة, عبد الحكيم (University of Eloued جامعة الوادي, 2021)
تتطرق هذه الدراسة التاريخية إلى إحدى السياسات الاستعمارية الفرنسية في الجزائر في المجال الاقتصادي بشكل عام والمجال العقاري بشكل خاص والمتمثلة في السياسة الفرنسية المتبعة في تفكيك الملكية العقارية للجزائريين 1830 – 1900 م فلقد أدرك الاستعمار الفرنسي بأن للأرض أهمية ودور كبير في تلاحم وترابط القبائل والأعراش الجزائرية، وتيقنوا أن إحكام القبضة على الشعب الجزائري لن يتم إلا بتفتيت هذه القبائل و الأعراش، وبحكم أن فرنسا دولة القانون - كما يقولون -، فإنها حاولت تقنين تفكيك الأرض و المجتمع الجزائري وتجلى ذلك واضحا في القوانين والمراسيم التي أصدرتها وأهمها قانون "سيناتوس كونسيلت " 1863م وقانون "وارني" 1873م، وقد كانت لهذه السياسة انعكاسات سلبية في معظمها على المجتمع الجزائري اقتصاديا ، اجتماعيا وسياسيا. This historical study evokes one of the French colonial politics in Algeria in the economical area in general and particularly in the real estate sphere, which is represented in the French policy used in disintegrated the Algerian real estate ownership in 1830-1900. The French colonial recognized that the territory has an important and a key role in the interconnection between the Algerian tribes. In addition, they were sure that taking control over the Algerian population won’t occur only by disintegrating these tribes and parts of the Algerian society . Since France was the country of law , it tried to divide the territory and it was abvious in the French colonial among them I cite: Cenatus Concult 1863 and Warnie in 1873 .In fact , this policy has a devastating impact on the Algerian society economically, socially ,and politically.